Autocracy, Inc: the dictators who want to run the world - Applebaum, Anne (Doubleday, 2024)
"From the Pulitzer-prize winning, New York Times bestselling author, an alarming account of how autocracies work together to undermine the democratic world, and how we should organize to defeat them We think we know what an autocratic state looks like: There is an all-powerful leader at the top. He controls the police. The police threaten the people with violence. There are evil collaborators, and maybe some brave dissidents. But in the 21st century, that bears little resemblance to reality. Nowadays, autocracies are underpinned not by one dictator, but by sophisticated networks composed of kleptocratic financial structures, surveillance technologies, and professional propagandists, all of which operate across multiple regimes, from China to Russia to Iran. Corrupt companies in one country do business with corrupt companies in another. The police in one country can arm and train the police in another, and propagandists share resources and themes, pounding home the same messages about the weakness of democracy and the evil of America. International condemnation and economic sanctions cannot move the autocrats. Even popular opposition movements, from Venezuela to Hong Kong to Moscow, don't stand a chance. The members of Autocracy, Inc, aren't linked by a unifying ideology, like communism, but rather a common desire for power, wealth, and impunity. In this urgent treatise, which evokes George Kennan's essay calling for "containment" of the Soviet Union, Anne Applebaum calls for the democracies to fundamentally reorient their policies to fight a new kind of threat"--